Public Private Collaboration Model In Spatial Data Infrastructure: Potential Elements - Raha Othman; Ku Ruhana binti Ku Mahamud; Muhamad Shahbani bin Abu Bakar (International Journal of Supply Chain Management, 2017)
The rapid development of Geospatial Technology locally and globally spurs the development of Spatial Data Infrastructure (SDI), mainly developed to help managing the growth of spatial data. Although the use of spatial data is reported as vast growth, SDI initiative is still reported to be below maturity due to low quality of data in terms of completeness and consistency, non-existence of custodian policy and information sharing act, and poor human capacity. These affected the full potential of spatial data as the main source to be used in development and decision-making activities. The availability of business centric data at the private sector further encourages the effort to collaborate these entities to gauge the full potential of SDI initiative. A conceptual model is proposed to solve issues in public-private collaboration in Spatial Data Infrastructure. The conclusion on exposure, acceptance, and spatial data sharing is based on the analysis of the outcome from the interview with seven entities related to spatial data infrastructure initiative. The outcome indicates that though the use is high, effectiveness of the geospatial technology is reported low due to the quality and heterogeneous data. Furthermore, the potential elements for collaborating public and private entities are proposed to optimise the utilisation of geospatial information, and create the synergy to spur the growth, hence sustaining the SDI initiative.